Hypercalcemia of Malignancy Induced by Parathyroid Hormone-related Protein in a Patient with Medullary Thyroid Carcinoma - Okutur, Kerem; Bes, Cemal; Cakir, Adile; Mazi, Emrah; Dirimen, Guliz; Cigerciogullari, Engin; Borlu, Fatih (Annals of Medical Research, 2021)
None